Identifying attributes and insecurity of a public-channel key exchange protocol using chaos synchronization - Han, Song; Chang, Elizabeth; Dillon, Tharam S; Hwang, M.; Lee, C. (Elsevier, 2009)
Klein et al. proposed a key exchange protocol using chaos synchronization. The first protocol comprises two parties with chaotic dynamics that are mutually coupled and undergo a synchronization process, at the end of which they can use their identical dynamical state as an encryption key. From cryptographic point of view, their key exchange protocol is a key agreement protocol. Klein et al. claimed that their key agreement can be carried out over a public channel. In order to increase the key space and decrease the precision of the calculation, they made an extension of the system to anetwork of N Lorenz equations. In this paper, we will provide a cryptanalysis of their key agreement protocol. We will first point out some weaknesses, and then show that their protocol is not secure against several attacks including impersonation attack.